Assessing the impacts of the COVID-19 wage supplement scheme: A microsimulation study - Glenn Abela (Central Bank of Malta, 2022)
Microsimulation models have been particularly useful when dealing with the economic welfare impact of COVID-19, particularly since such models offer a way to obtain timely and policy-relevant information in the absence of detailed household-level survey data. This study uses EUROMOD, a static tax-benefit microsimulation model calibrated for Malta, to evaluate the microeconomic impact of the wage supplement scheme introduced in Malta in response to the COVID-19 pandemic for the year 2020. Results suggest that the wage supplement scheme had a number of positive effects. First, it dampened average income losses, both across the income distribution and within economic sectors irrespective of the extent to which these were impacted. In particular, the results show that the scheme's impact across the income spectrum was progressive in the sense that it shielded the lowest earners relatively more. Poverty rates are invariably lower under the wage supplement scenario, than under a scenario where the scheme is not enacted, whilst its impacts on income inequality are ambiguous. Importantly, the size of the shock suffered by the worst-hit households declines markedly in the presence of the scheme. Future work can benefit from the availability of household survey data to conduct a more thorough assessment of the impacts this study attempts to measure, and in so doing, serve as a validation tool against which simulation exercises such as this can be compared.
Keywords: 330; Lohnersatzleistungen; Coronavirus; Öffentliche Sozialleistungen; Wirkungsanalyse; Mikrosimulation; Malta